Multichannel photodissociation dynamics in CS2 studied by ultrafast electron diffraction. Issue 25 (16th June 2022) - Razmus, Weronika O.; Acheson, Kyle; Bucksbaum, Philip; Centurion, Martin; Champenois, Elio; Gabalski, Ian; Hoffman, Matthias C.; Howard, Andrew; Lin, Ming-Fu; Liu, Yusong; Nunes, Pedro; Saha, Sajib; et al.
Abstract : The structural dynamics of photoexcited gas-phase carbon disulfide (CS2 ) molecules are investigated using ultrafast electron diffraction. Abstract : The structural dynamics of photoexcited gas-phase carbon disulfide (CS2 ) molecules are investigated using ultrafast electron diffraction. The dynamics were triggered by excitation of the optically bright 1 B2 ( 1 Σu + ) state by an ultraviolet femtosecond laser pulse centred at 200 nm. In accordance with previous studies, rapid vibrational motion facilitates a combination of internal conversion and intersystem crossing to lower-lying electronic states. Photodissociation via these electronic manifolds results in the production of CS fragments in the electronic ground state and dissociated singlet and triplet sulphur atoms. The structural dynamics are extracted from the experiment using a trajectory-fitting filtering approach, revealing the main characteristics of the singlet and triplet dissociation pathways. Finally, the effect of the time-resolution on the experimental signal is considered and an outlook to future experiments provided.